Characterization of myeloperoxidase and its contribution to antimicrobial effect on extracellular traps in flounder (Paralichthys olivaceus) - Gan, Qiujie; Chi, Heng; Dalmo, Roy Ambli; Meng, Xianghu; Tang, Xiaoqian; Xing, Jing; Sheng, Xiuzhen; Zhan, Wenbin (Frontiers in Immunology, 2023)
Myeloperoxidase (MPO) is a cationic leukocyte haloperoxidase and together with other proteins, they possess activities against various microorganisms and are involved in extracellular trap (ET) formation. The present work describes the gene and deduced protein sequences, and functions of MPO in flounder (PoMPO). The PoMPO possesses a 2313 bp open reading frame (ORF) that encodes a protein of 770 amino acids. The highest PoMPO mRNA expression levels were found in the head kidney, followed by peritoneal cells, gill, spleen, skin, muscle, and liver. PoMPO was expressed in MHCII+ and GCSFR+ cells which indicated that PoMPO mainly is expressed in flounder macrophages and granulocytes. Bacterial lipopolysaccharide-stimulated peritoneal leukocytes showed an increased protein level of PoMPO while it seemed that LPS also promoted the migration of MPO+ cells from the head kidney into the peripheral blood and peritoneal cavity. After phorbol 12-myristate 13-acetate (PMA) or bacterial stimulation, flounder leukocytes produced typical ET structures containing DNA with decoration by MPO. The ETs containing DNA and PoMPO effectively inhibited the proliferation of ET-trapped bacteria. Blocking PoMPO with antibodies decreased the enzymatic activity, which attenuated the antibacterial activity of ETs. This study pinpoints the involvement of ETs in flounder innate responses to pathogens.